Eucalyptus and Ipomoea nil phytotoxicity after herbicide application - Freitas e Silva, Ilca Puertas de; Ferreira Silva Junior, Josué; Antonio Carbonari , Caio; Domingues Velini , Edivaldo; Araldi de Castro , Rosilaine; Tropaldi , Leandro; Domingos Rodrigues , João (Revista Brasileira de Engenharia de Biossistemas, 2023)
The presence of weeds in forest estates is considered one of the biggest problems in the implantation, maintenance, and renovation of eucalyptus plantations. This research aims to evaluate the phytotoxicity of herbicides on eucalyptus and I. nil. The experiment was installed inside a greenhouse in a completely randomized design with five replications. The treatments consisted of the application of 0.2% (v/v) adjuvant with the herbicides: atrazine (2250 g i.a. ha-1), clomazone (720 g i.a. ha-1), sulfentrazone (600 g i.a. ha-1), glyphosate (1440 g i.a. ha-1), and control. The following variables were analyzed: electron transport rate (ETR), water consumption, and plant phytotoxicity. For I. nil plants treated with atrazine, it was possible to detect phytotoxicity previous to the appearance of symptoms in the visual analysis, due to the inhibition of ETR at 24 hours after application (HAA). The highest levels of phytotoxicity for eucalyptus and I. nil were obtained by glyphosate and sulfentrazone, respectively.